Differences in postural strategies between children with and without ADHD in tasks of static and dynamic balance - Christ, Tabea; Boström, Kim Joris; Wagner, Heiko; Bohn, Christiane (Frontiers in Human Neuroscience, 2025)
BackgroundMany children with ADHD experience challenges with balance and postural control, unlike their unaffected peers. While postural sway has been extensively studied in this patient group, less is known about the postural strategies employed to maintain equilibrium. This study extends the examination of hip and ankle postural strategies by including an upper body strategy involving movements of the head, arms, and trunk to regain balance. The aim was to investigate the differences in postural control strategies between children with and without ADHD.MethodsForty one children (17 diagnosed with ADHD, 24 unaffected controls) with a mean age of 10.0 ± 1.4 years participated in the study. For the assessment of static balance, a 25-s one-leg stand was conducted. Dynamic balance was evaluated by balancing on a narrow wooden beam. Kinetic data was recorded using Kistler force plates. Kinematic data was collected with the Qualisys motion capture system. Joint torque amplitudes were calculated using an inverse-dynamics approach employing the Myonardo software.ResultsChildren with ADHD produced significantly higher joint torques during static and dynamic balancing compared to neurotypical children in the ankle and upper body joint group. Torque amplitudes of the upper body joints were 11% and 7.5% higher for the dynamic and static balance tasks, respectively, and 22% and 20% higher for the ankle joint. For hip joint torque variation, the ADHD group exhibited 25% and 34% lower joint torques for the dynamic and static balance tasks, respectively.ConclusionImpaired proprioception and neuromuscular control are common in children with ADHD and may present as reduced precision in muscle activation. Cerebellar deficits in this patient group negatively affect balance and coordination. Such deficits likely interfere with the adjustment of joint torques involved in maintaining balance and stability. Children with ADHD appear to struggle to efficiently employ and combine postural strategies as required by the given task. Assessments of balance and postural control in children with ADHD are indispensable for developing tailored interventions and thus reducing injury risk and promote wellbeing.